Identification of molecular determinants of cell culture growth characteristics of Enterovirus 71 - Yee, Isabel Pin Tsin *; Tan, Kuan Onn *; Othman, Lekhsan; Poh, Chit Laa * (BioMed Central, 2016)
Hand, foot and mouth disease is caused by Enterovirus 71 (EV-A71) and Coxsackieviruses. EV-A71 infection is associated with high fever, rashes and ulcers but more severe symptoms such as cardiopulmonary failure and death have been reported. The lack of vaccines highlighted the urgency of developing preventive agents against EV-A71. The molecular determinants of virulent phenotypes of EV-A71 is unclear. It remains to be investigated if specific molecular determinants would affect the cell culture growth characteristics of the EV-A71 fatal strain in Rhabdomyosarcoma (RD) cells. In this study, several genetically modified sub-genotype B4 EV-A71 mutants were constructed by site directed mutations at positions 158, 475, 486, 487 and 5262 or through partial deletion of the 5′-NTR region (Δ 11 bp from nt 475 to 486) to generate a deletion mutant (PD). EV-A71 mutants 475 and PD caused minimal cytopathic effects, produced lowest viral RNA copy number, viral particles as well as minimal amount of viral protein (VP1) in RD cells when compared to mutants 158, 486, 487 and 5262. The molecular determinants of virulent phenotypes of EV-A71 sub-genotype B4 strain 41 (5865/Sin/ 000009) were found to differ from the C158 molecular determinant reported for the fatal EV-A71 sub-genotype B1 strain (clinical isolate 237). The site-directed mutations (SDM) introduced at various sites of the cDNA affected growth of the various mutants when compared to the wild type. Lowest viral RNA copy number, minimal number of plaques formed,higher infectious doses required for 50% lethality of RD cells and much reduced VP1 of the EV-A71 sub-genotype B4 strain 41 genome was attained in mutants carrying SDM at position 475 and through partial deletion of 11 bp at the 5′-NTR region.